Socio-Cultural Study of Nutrition in Families of Stunted Toddlers in Coastal Communities in Jember Regency - Nafikadini, Iken; Leersia Yusi; Globila Nurika (Jurnal Promkes: The Indonesian Journal of Health Promotion and Health Education, 2024)
Background: Cultures, traditions, or habits that exist in society, such as dietary restrictions and wrong eating patterns, can lead to increased nutritional problems, especially in toddlers, which ultimately impacts their growth and development. Low-income family parenting patterns in feeding and primary health care for toddlers can also increase the incidence of stunting in toddlers. This could be the cause of the stunting rate in the Jember Regency, especially in coastal areas. Dietary problems, including stunting, in coastal areas should be less likely to occur because the availability of high-protein animal foods such as fish is quite high, but Curahnongko Village is included in the stunting locus area in Jember Regency. Aims: This research aims to describe the socio-cultural nutrition and parenting styles of toddlers in Curahnongko Village. Methods: The study used qualitative and research methods with a case study approach. Results: The socio-culture during pregnancy in the coastal communities of Jember Regency regarding TTD consumption, routine check-ups, taboos during pregnancy, and visits to midwives are quite good. Socio-culturally during the breastfeeding period, it can be concluded that all informants carried out Early Breastfeeding Initiation (IMD). Socio-culturally during the feeding period for toddlers, all informants do not give food other than breast milk to babies when they are born. Conclusion: The socio-cultural aspect that appears to influence the occurrence of stunting is during the feeding period for toddlers, namely the frequency of children's snack consumption outside the home.